Grain refinement of Mg-14Li alloy by Sn addition and large strain rolling - Jia, Haoyang; Guo, Zhengyou; Wu, Ruizhi; Zhang, Shun (Frontiers in Materials, 2022)
Mg-Li alloy is the lowest density structural metal, which has great potential for various industrial applications. Although Mg-Li alloy has excellent plasticity, it has low strength and requires further strengthening. In this study, the grain size of Mg-14 wt% Li alloy was refined to 15.7 μm by the addition of 6 wt% Sn, the initial grain size of as-cast Mg-14Li alloy was 180 μm. Furthermore, the grain size of Mg-14Li-6Sn was further refined to 400 nm by the subsequent large strain rolling (LSR). The yield strength of the ultra-fine grained Mg-14Li-6Sn reached 160 MPa, and the elongation was not sacrificed but increased to 30% compared with the as-cast alloy (14%). The microstructural evolution was characterized by optical microscopy (OM), scanning electron microscope (SEM) and transmission electron microscopy (TEM). The high ductility of the ultra-fine grained Mg-14Li-6Sn is attributed primarily to the dynamic recovery, and the increase in strength is mainly due to the grain refinement.